Analiza odrskega govora - Žavbi Milojević, Nina (Slavistična revija, 2013)
The article examines the process of writing a playscript, which somewhat differs from the dramatic text because of dramaturgical cuts, added text, and changes in language varieties. The focus is mainly on the stage speech of individual actors who use prosodic elements (intonation, register, timbre, pause, loudness, tempo, voice modulation), mimic, and gesture to creatively portray individual characters.
Keywords: "Hlapci"; Berger, Matjaž, 1964-; Cankar, Ivan, 1876-1918; fonetika; Hlapci: Komentirana izdaja; Ivan Cankar: Hlapci; odrski jezik; phonetics; playscript; prosodic element; prozodična sredstva; Slovene drama; Slovene literature; slovenska dramatika; slovenska književnost; stage speech; uprizoritveno besedilo